Untargeted plasma metabolomics based on liquid chromatography-mass spectrometry for the analysis of Dendrobium officinale on canine immunity and antioxidant status - Yang, Jie; Yang, Xiaobing; Liu, Baoguo; Shi, Baiguan; An, Lihong; Zhang, Dongtao; Gao, Qiaoxian; Yang, Wenzhi; Xin, Guosheng (Frontiers in Veterinary Science, 2025)
Dendrobium officinale Kimura et Migo (D. officinale) is a valuable traditional Chinese herb, rich in bioactive compounds like polysaccharides and flavonoids. It is recognized for its immunomodulatory and antioxidant properties. However, its impact on canine metabolic health remains unexplored. This study investigated the effects of Dendrobium officinale supplementation on nutrient digestibility, blood biochemical parameters, antioxidant activity, and serum metabolomics in domestic poodles. Thirty-two ((5.20 ± 0.26 kg)) healthy female poodles were randomly divided into four groups and fed diets containing 0% (control), 0.5%, 1%, or 2% D. officinale for 45 days. The results showed that D. officinale supplementation did not affect the apparent digestibility of dry matter (DM), crude protein (CP), crude fat (EE), crude ash (Ash), calcium (Ca) and phosphorus (P) in poodles (p > 0.05). The peak IgM concentration (1.04 g/L) was observed at a 1% supplementation level, while optimal TP and GLB levels (69.72 g/L and 34.67 g/L, respectively) were noted at 0.5% supplementation. The highest CAT activity (1.95 U/mL) and T-AOC (7.12 U/mL) were observed at a 1% level, while the highest GSH-Px activity (1630.56 U/mL) was recorded at 2% supplementation level. Metabolomic analysis identified ten significantly altered serum metabolites involved in oxidative stress, inflammatory mediation, and energy metabolism. Key metabolic pathways influenced included arachidonic acid, caffeine, pyruvate, and amino acid metabolism.These findings suggest that D. officinale enhances immune and antioxidant function in poodles without affecting nutrient digestion, likely through modulation of critical metabolic pathways. A supplementation level of 0.5% to 1% is recommended to achieve these beneficial effects.